Comprehensive pregnancy dental benefits improved dental coverage and increased dental care utilization among Medicaid-enrolled pregnant women in Virginia - Naavaal, Shillpa; Harless, David W. (Frontiers in Oral Health, 2022)
Objectives. To evaluate the changes in dental insurance and utilization among pregnant women before and after the pregnancy Medicaid dental benefit policy implementation in 2015 in Virginia. Methods. We used pooled cross-sectional data from six cycles of the Virginia Pregnancy Risk Assessment Monitoring System on women aged ≥21 years. Using logistic regression models and a difference-in-difference design, we compared the effects of policy implementation on dental insurance and utilization between pre-policy (2013-2014) and post-policy period (2016-2019) among women enrolled in Medicaid (treatment, N=1,105) versus those with private insurance (control, N=2,575). A p-value of 0.05 was considered significant. Results. Among Medicaid-enrolled women, the report of dental insurance (71.6%) and utilization (37.7%) was higher in the post-period compared to their pre-period (44.4% and 30.3%, respectively) estimates but still remained lower than the post-period estimates among women with private insurance (88.0% and 59.9%, respectively). Adjusted analyses found that Medicaid-enrolled women had a significantly greater change in the probability of reporting dental insurance in all post-period years than women with private insurance, while the change in the probability of utilization only became statistically significant in 2019. In 2019, there was a 16 percentage point increase (95% CI = 0.05, 0.28) in the report of dental insurance and a 17 percentage point increase (95% CI = 0.01-0.33) in utilization in treatment group compared to controls. Conclusions. The 2015 pregnancy Medicaid dental benefit increased dental insurance and dental care utilization among Medicaid-enrolled women and reduced associated disparities between Medicaid and privately insured groups.